Both R5 and X4 Human Immunodeficiency Virus Type 1 Variants Persist during Prolonged Therapy with Five Antiretroviral Drugs - van Rij, Ronald P. (American Society for Microbiology, 2002)
A viral reservoir of human immunodeficiency virus type 1 (HIV-1)-infected, resting CD4(+) T cells persists despite suppression of plasma viremia by combination antiretroviral therapy. In a longitudinal analysis of three patients treated with a five-drug regimen, both R5 and X4 HIV-1 variants persisted in the cellular reservoir for up to 3 years.